Biblical Epistemology for Adventist Scholarship? A Working proposal - Canale, Fernando (2011)
Since the creation of the first Adventist Universities early in the second half of the twentieth century, the Seventh-day Adventist church has engaged in scientific re- search in several secular and theological scholarly disciplines that involve the use of human reason and methodologies. Because, normally, researchers select and use methodologies based on the current consensus of their scholarly disciplines, we have to assume Adventist scholars do the same. Seldom do scientists take time to analyze, evaluate, and criticize the intellectual tools they use. This article deals with the necessity of implement a biblical epistemology for developing researches with an Adventist profile.